Investigation of quasi-static indentation on sandwich structure with GFRP face sheets and PLA bio-inspired core: Numerical and experimental study. (March 2023) - Gunasegeran, Muthukumaran; P., Edwin Sudhagar; Vasudevan, Maiarutselvan; Ramamoorthy, Manoharan; Arumugam, Anandababu
Abstract: Composite materials incorporated in naval, aerospace, and automobile structures are exposed to unforeseen damages, which seriously damage their mechanical performance. In particular, the existence of hardly visual impairment on the in-service composite structures is a critical issue that highlights the severity of structural safety in an aircraft. The ability of these materials to sustain multiple impacts requires an understanding of the impact energy absorption to improve the material's damage tolerance. The present study investigates the energy absorption, load response, failure modes, and damage mechanics under the quasi-static indentation of a sandwich structure. The structure comprises bio-inspired Poly-lactic Acid (PLA) core and Glass Fibre Reinforced Polymer (GFRP) laminates, used in real naval and aeronautical structures, under repeated low-velocity impact with reduced energies and quasi-static indentation. In addition, a lightweight sandwich structure's damage performance is greatly influenced by its core geometry. Therefore, choosing an appropriate core structure is critical. A Numerical model is developed for the composite structure under quasi-static indentation loads, considering suitable material properties and damage models for the core and face sheets. These results are then compared with the experimental investigation. The load–displacement response and the energy absorption characteristics of the sandwich structure showed good agreement for the experimental and numerical analysis results. Highlights: The use of QSI tests facilitates design exploration of dynamic material failures without requiring extensive computational resources. The bio-inspired structure's energy absorption behaviour is largely influenced by its core geometric design. And in comparison with the complete models, the bottom face sheet exhibits a reduced energy absorption, while the top fact sheet shows an increased absorption. The layer-wise energy dissipations are expressed for the discrete sections of composite plate with a bio-inspired PLA core. Post quasi-static indentation tests, the samples were characterized using C-scan imaging and optical microscopy.